2017
DOI: 10.1038/s41598-017-04440-y
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependent Uptake and Hemolytic Effect of Zinc Oxide Nanoparticles on Erythrocytes and Biomedical Potential of ZnO-Ferulic acid Conjugates

Abstract: Despite zinc oxide nanoparticles (ZnONPs) being increasingly used as carriers in biomedical fields due to their multifaceted properties and therapeutic importance, better understanding of the mechanisms and cellular consequences resulting from their interaction with cells and cellular components has been warranted. In the present study, we investigate the size-dependent interaction of ZnONPs on RBCs, and its impact on cell viability, DNA damage, ROS generation and morphological changes, employing cellular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Before administering SeNPs to RA rats, we tested the stability of SeNPs in water and saline, showing that these are not suitable media. A recent study shows that phytochemical compound could serve as anti-aggregation substances [17]. Since our focus is on the effect of SeNPs against RA, we intended to test a phytochemical already proved to have anti-RA effects; therefore, we tested the anti-aggregation property of CA [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before administering SeNPs to RA rats, we tested the stability of SeNPs in water and saline, showing that these are not suitable media. A recent study shows that phytochemical compound could serve as anti-aggregation substances [17]. Since our focus is on the effect of SeNPs against RA, we intended to test a phytochemical already proved to have anti-RA effects; therefore, we tested the anti-aggregation property of CA [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Se nanoparticles (SeNPs) shows less in vivo toxicity when compared with normal-size Se [15,16]. Dispersed elemental nanoparticles aggregate spontaneously in water or saline [17], which are 2 major media used in drug delivery. Therefore, maintaining the nanoparticle size in drug delivery medium is of paramount importance to achieve the maximum therapeutic effect of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…As the hemolytic effect of any analyte plays a crucial role in understanding the cellular mechanism then hemolysis assay is an important part of scientific research . The hemolytic effect of cartap in different concentration were analyzed so the incubation of human red blood cells in the presence of varies concentrations of cartap, showed that the lysis percentage (lys%) increased with respect to its concentration.…”
Section: Resultsmentioning
confidence: 65%
“…Copper has also been observed for having the potency to form nanocomposite in presence of ferulic acid [24]. The studies of complex formulation of this flavonoid along with iron [25] and zinc [26] have also been done. Although many other groups have been working in the field of metal nanocomposite formation by various experimental approaches, but the study of the interaction between the drug molecule and metal atom has not yet been done extensively.…”
Section: Resultsmentioning
confidence: 99%